Why only feedback? Including feed up and feed forward improves non-linguistic aspects of L2 writing. (May 2023) - Zarrinabadi, Nourollah; Rezazadeh, Mohsen
This study examined the effect of feedback, feed up (comments on goals and students' success in achieving goals) and feed forward (comments on the next step in learning during the semester) on writing motivation, writing self-efficacy, and writing anxiety. Two hundred and ten female intermediate language learners (agemean = 17.2) were assigned to seven experimental conditions: feedback, feed up, feed forward, feedback + feed up, feedback + feed forward, feed up + feed forward, and feedback + feed up + feed forward ( n = 30 for each group). Based on group assignment, the participants received feedback, feed up, and feed forward for 12 sessions and took writing motivation, writing self-efficacy, and writing anxiety scales as pretest and posttest. The results of MANOVA and paired samples t -test comparisons indicated that groups that received feedback significantly improved in terms of self-efficacy. In addition, groups who received feed up and feed forward significantly improved in terms of writing motivation. The results also showed that the combination of feedback, feed up and feed forward could decrease learners' writing anxiety. Based on the findings of the study, it is recommended that teachers present feed up and feed forward along with feedback to improve non-linguistic aspects of L2 writing among their students.